The Role of Forensic Accounting Skills on Fraud Detection with Self-Efficacy as an Intevening Variable and CAATS as Moderating Variable: a Study in Investigation Unit of BPK RI - Fauzi Nursyahdani; Murtanto Murtanto (International Journal of Business and Quality Research, 2024)
This research aims to investigate the influence of forensic accounting skills on fraud detection through an auditor's self-efficacy. Additionally, the study introduces CAATTs as a moderating variable. Hypotheses were tested using SPSS. The research finds that forensic accounting skills, including technical and analytical skills, psycho-social skills, and accounting and auditing skills, have a positive and significant impact on auditor self-efficacy. Conversely, effective communication skills were found to have no significant influence on auditor self-efficacy. Furthermore, self-efficacy and CAATT were found to positively and significantly influence fraud detection. However, CAATT was found unable to moderate the influence of self-efficacy on fraud detection. These findings imply the need for auditor in BPK RI to focus on enhancing technical and analytical, psychosocial, and accounting and auditing skills to boost their confidence in detecting fraud within audited entities. Future research is recommended to broaden the scope beyond investigative units to encompass all units within the BPK RI to explore broader variables impacting fraud detection as part of anti-corruption efforts.